Rivaroxaban Use in Patients with Hemoglobinopathies. (4th May 2017) - Apostolou, Chrysoula; Klonizakis, Philippos; Mainou, Maria; Kapsali, Eleni; Kafantari, Katerina; Kotsiafti, Aggeliki; Vetsiou, Evaggelia; Vakalopoulou, Sofia; Vlachaki, Efthymia
Abstract: The use of rivaroxaban in patients with hemoglobinopathies and thrombotic events has not been studied extensively. Here we present eight cases of such patients, five receiving rivaroxaban for stroke and systemic embolism prevention due to non-valvular atrial fibrillation and three for deep vein thrombosis treatment. The follow-up period ranged from 6 to 34 months. During this period none of the patients experienced any thrombotic or bleeding event.There were no other adverse events reported. Further studies with larger numbers of patients with hemoglobinopathies are needed to determine the use of rivaroxaban and ensure its safety in this patient setting.